ERA EKSPLOITASI SUMBERDAYA ALAM Dl AMERIKA SERIKAT - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
It was since the pioneer era, the colony era and the frontier era to the West. Before the pioneer era, the first American people tent to use the natural resources as the daily basic need (self-suffiecient). When the first settlers arÂ¬rived in the new world, America, they depended first of all on natural reÂ¬sources to survive. They thought that America's resources were unlimited. In the late 19th century when the migration to the West was closed the American natural environment had been depleted over the country.